The The locating-chromatic number for certain operation of pizza graphs - Irawan, Agus (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study investigates the location chromatic number resulting from specific operations on pizza graphs. The location chromatic number of a graph extends the concept of vertex coloring and graph partition dimension. This research aims to deepen the understanding of how certain operations influence the location chromatic number of pizza graphs. By conducting rigorous mathematical analysis, this study demonstrates the effects of particular operations on the chromatic properties of these graphs. The results provide valuable insights into the characteristics of pizza graphs, which are known for their complex and irregular structures. These findings contribute to the broader development of graph theory, particularly in understanding modified graph structures. Additionally, the research highlights the potential applications of these concepts in various scientific and mathematical domains. This study serves as a foundation for future exploration of chromatic properties in more complex and diverse graph structures.